2018
DOI: 10.1111/aas.13239
|View full text |Cite
|
Sign up to set email alerts
|

The role of prehabilitation in frail surgical patients: A systematic review

Abstract: This systematic review focuses on prehabilitation in frail surgical patients and reports that evidence supporting any outcome is limited, despite high feasibility and acceptability. There is a need for large randomised controlled trials to better establish the effects of prehabilitation in frail patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…Sarcopenia was an outcome in 4 studies. 21,24,27,31 Two studies were defined according to the European Working Group on Sarcopenia in Older People. 21,25,30 Participants who had (1) low muscle mass, (2) low muscle strength, and/or (3) low physical performance were classified as having sarcopenia.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Sarcopenia was an outcome in 4 studies. 21,24,27,31 Two studies were defined according to the European Working Group on Sarcopenia in Older People. 21,25,30 Participants who had (1) low muscle mass, (2) low muscle strength, and/or (3) low physical performance were classified as having sarcopenia.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…After observing that physical exercise can reduce frailty, clinicians have used this knowledge to include physical exercise in prehabilitation programs for older frail adults undergoing scheduled surgery, as a way to optimize their physical condition and decrease possible negative outcomes linked to surgery and hospitalization. Usual prehabilitation programs that include physical and nutritional interventions have demonstrated to reduce the incidence of post-operative complications, shorten hospital stay and improve healthrelated quality of life [118,119], also in frail patients [120]. Regarding delirium, we are beginning to observe positive effects of prehabilitation programs with a reduction in delirium incidence [121], although more studies are needed.…”
Section: Delirium Prevention By Targeting Frailty With Physical Exercisementioning
confidence: 99%
“…Recent studies demonstrated that prehabilitation in frail patients, consisting of physical exercises, can be helpful in decreasing the amount of adverse postoperative outcomes, like delirium and hospital length of stay [ 47 , 48 ]. Possibly, prehabilitation can also help frail patients to transition to a non-frail state after surgery [ 49 ]. Therefore, the results of this study may lead to a more effective shared decision-making process when considering treatment options, by providing more insight in the postoperative frailty course of the patient [ 50 ].…”
Section: Discussionmentioning
confidence: 99%